Process evaluation of the Belgian one-month-without alcohol campaign 'Tournée Minérale': a mixed method approach - Annelies Thienpondt; Jelle Van Cauwenberg; Joris Van Damme; Benedicte Deforche (BMC, 2024)
Abstract Background The Tournée Minérale campaign [TMC] is a mass media prevention campaign challenging Belgian adults to refrain from alcohol during one month. A process evaluation may help us better understand the effect of TMC and to formulate recommendations for future editions. The current study aimed to examine reach, experiences, perceived effectiveness and maintenance of TMC. Methods A mixed method design was used to assess the process, using pre- and post-questionnaires (n = 49.022, 44.5 ± 13.1 years old, 37.0% men) and focus groups (n = 31, 47.3 ± 14.3 years old, 33.3% men). Results Most campaign materials were considered useful and/or motivating. Facilitators for taking part in TMC were connectedness with other participants, stimulus control (e.g. removing alcohol at home) and a supportive social environment. Most difficulties were encountered with abstaining during social occasions as participants had to change a habit or find alternative non-alcoholic beverages. Participants reported both beneficial (e.g. sleeping better) and adverse effects (e.g. drinking more soft drinks). Conclusions Future editions of TMC should try to decrease perceived adverse effects (e.g. by providing attractive non-alcoholic beverages) and can benefit from having a forum where people can share experiences.